2019
DOI: 10.1186/s13568-019-0857-7
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of silver nanoparticles in combination with ketoconazole against Malassezia furfur

Abstract: Malassezia furfur is lipophilic and lipid-dependent yeast, inhabitant of human skin microbiota associated with several dermal disorders. In recent years, along with the advances in nanotechnology and the incentive to find new antimicrobial drugs, there has been a growing interest in the utilization of nanoparticles for the treatment of skin microbial infections. This work aimed to study the in vitro inhibitory activity of silver nanoparticles (AgNP) against 41 M. furfur clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 60 publications
0
33
0
Order By: Relevance
“…Silver NPs are one of the most frequently tested against microorganisms with well documented antifungal effects [47,48]. Additionally, combining silver NPs with ketoconazole, another azole drug, was also investigated and showed high inhibition rate when applied as gel [49]. Synergistic inhibition effect was also proved for silver NPs combined with epoxiconazole [50].…”
Section: Of 20mentioning
confidence: 99%
“…Silver NPs are one of the most frequently tested against microorganisms with well documented antifungal effects [47,48]. Additionally, combining silver NPs with ketoconazole, another azole drug, was also investigated and showed high inhibition rate when applied as gel [49]. Synergistic inhibition effect was also proved for silver NPs combined with epoxiconazole [50].…”
Section: Of 20mentioning
confidence: 99%
“…Upon dissociation, Cu 2+ can then be reduced by fungal proteins for uptake. More recently, metals in the form of nanoparticles have gained interest for use as antifungals, which has fueled the escalation of nanoparticle production [ 8 , 9 , 10 ]. Nanoparticles are particles that range from 1 to 100 nm in size and vary in shape, physiochemical, optical, and biological properties [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These important materials have attained considerable interest lately because of their good conductivity [ 4 ], chemical stability [ 5 ], catalytic [ 6 ], and antimicrobial activity [ 7 , 8 ]. It has been shown that AgNPs exhibit strain-specific antimicrobial activity against different pathogenic bacterial strains [ 9 ], as well as against toxigenic species of fungi [ 10 , 11 ]. Similarly, due to their distinctive features, these nanoparticles have prognostic applications against various diseases, such as those caused by bacteria, fungi, and viruses, including tuberculosis, acquired immunodeficiency syndrome, and retinal neovascularization [ 12 ].…”
Section: Introductionmentioning
confidence: 99%